Molecular hydrogen and catalytic combustion in the production of hyperpolarized 83Kr and 129Xe MRI contrast agents - Rogers, Nicola J.; Hill-Casey, Fraser; Stupie, Karl F.; Six, Joseph S.; Lesbats, Clémentine; Rigby, Sean P.; Fraissard, Jacques; Pavlovskaya, Galina E.; Meersmann, Thomas (National Academy of Sciences, 2016)
Hyperpolarized (hp) 83Kr is a promising MRI contrast agent for the diagnosis of pulmonary diseases affecting the surface of the respiratory zone. However, the distinct physical properties of 83Kr that enable unique MRI contrast also complicate the production of hp 83Kr. This work presents a radically new approach in the generation of hp 83Kr that can likewise be utilized for the production of hp 129Xe. Molecular nitrogen, typically used as buffer gas in spin exchange optical pumping (SEOP), was replaced by molecular hydrogen without penalty for the achievable hyperpolarization. In this particular study, the highest obtained nuclear spin polarizations were P = 29 % for 83Kr and P = 63 % for 129Xe. The results were reproduced over many SEOP cycles despite the laser induced on-resonance formation of rubidium hydride (RbH). Following SEOP, the H2 was reactively removed via catalytic combustion without measurable losses in hyperpolarized spin state of either 83Kr or 129Xe. Highly spin polarized 83Kr can now be purified for the first time to provide high signal intensity for the advancement of in vivo hp 83Kr MRI. More generally, a chemical reaction appears as a viable alternative to the cryogenic separation process, the primary purification method of hp 129Xe for the past 2 . decades. The inherent simplicity of the combustion process will facilitate hp 129Xe production and should allow for on-demand continuous flow of purified and highly spin polarized 129Xe.